2019
DOI: 10.26719/emhj.18.010
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, practices and attitudes of physicians towards evidencebased medicine in Egypt

Abstract: A cross-sectional study was performed in Tanta University Hospitals, which has 1962 beds providing secondary and tertiary healthcare services to 559 532 patients per year. The total number of working physicians is 2138 (8). The study subjects were physicians working at Tanta University Hospitals based on the following inclusion criteria: residents, demonstrators, and assistant lecturers working at different departments of Tanta University Hospitals. Exclusion criteria included: physicians who spent < 3 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 8 publications
8
31
4
Order By: Relevance
“…Most of the participants in this study reported positive to very positive attitudes, both collegially and individually. This is congruent with other studies in the region that showed that clinicians generally have a favorable view of EBM [ 13 , 26 , 27 ]. These studies also cited that despite having positive attitudes towards EBM, this was not necessarily translated into aptitude or knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the participants in this study reported positive to very positive attitudes, both collegially and individually. This is congruent with other studies in the region that showed that clinicians generally have a favorable view of EBM [ 13 , 26 , 27 ]. These studies also cited that despite having positive attitudes towards EBM, this was not necessarily translated into aptitude or knowledge.…”
Section: Discussionsupporting
confidence: 92%
“…Most of the participants in this study reported positive to very positive attitudes, both collegially and individually. This is congruent with other studies in the region that showed that clinicians generally have a favorable view of EBM 13,20,21 . These studies also cited that despite having positive attitudes towards EBM, this was not necessarily translated into aptitude or knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…The barriers to practising EBM were patient overload (68.1%), lack of tie (60.1%), colleagues' attitude (47%), lack of skills (46.7%) and fear of criticism (44.5%). 2 Lack of time has been a common barrier reported among physicians for the past 20 years. 2 3 It has been suggested that for clinicians to have a good grasp of EBM, they would need to read at least 19 original articles every day of the year.…”
Section: Introductionmentioning
confidence: 99%